GERAKAN WAKAF TUNAI DI DESA TANGGUNGHARJO KECAMATAN GROBOGAN (UIN Sunan Kudus, 2016)
Waqf is essentially a collection of endowment that designation in accordance with the desire by a berwakaf it. Someone who has been donating his wealth for the sake of goodness always let the treasure was exploited anyone accordance designation of waqf it. Many things influence whether or not the applicable regulation or law. For cash waqf empowerment, community and religious leaders even villages do not yet know its laws.